2022
DOI: 10.3390/genes13040641
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Transposable Elements and the Identification of Candidate Centromeric Elements in the Prunus Subgenus Cerasus and Its Relatives

Abstract: The subgenus Cerasus and its relatives include many crucial economic drupe fruits and ornamental plants. Repetitive elements make up a large part of complex genomes, and some of them play an important role in gene regulation that can affect phenotypic variation. However, the variation in their genomes remains poorly understood. This work conducted a comprehensive repetitive sequence identification across the draft genomes of eight taxa of the genus Prunus, including four of the Prunus subgenus Cerasus (Prunus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 79 publications
2
9
0
Order By: Relevance
“…In the chicken karyotype, several centromere-specific types of satDNA are highly similar to retrotransposons [ 127 ]. In the centromeres of Prunus species, a highly conserved monomer unit of 166 bps has been identified from assembled genomes and sequencing reads, with varying signal intensities in fluorescence in situ hybridization (FISH) experiments, which indicates that the centromeric regions of this genus are enriched with this sequence [ 128 ].…”
Section: Is the Centromeric Region A Hotspot Of The Emergence Of De N...mentioning
confidence: 99%
“…In the chicken karyotype, several centromere-specific types of satDNA are highly similar to retrotransposons [ 127 ]. In the centromeres of Prunus species, a highly conserved monomer unit of 166 bps has been identified from assembled genomes and sequencing reads, with varying signal intensities in fluorescence in situ hybridization (FISH) experiments, which indicates that the centromeric regions of this genus are enriched with this sequence [ 128 ].…”
Section: Is the Centromeric Region A Hotspot Of The Emergence Of De N...mentioning
confidence: 99%
“…Repetitive DNA sequences, as a vital source of FISH probes, have been broadly applied in many plants [ 14 ], especially for peanut [ 17 , 58 ] and wheat [ 59 , 60 ]. However, the three probes that we identified previously could not be used for chromosome identification due to their locations at the terminus of chromosomes, which was due to the lower content or variety of tandem repeat sequences in their genomes [ 61 ]. Therefore, we used a combination of genomic data and oligo pool synthesis techniques to design a chromosome-specific single-copy oligonucleotide pool that could be used to accurately identify chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Three oligo probes were designed from species-specific satellite sequences (monomer lengths 102 bp, 149 bp, and 159 bp) that we identified previously ( Supplementary Figure S9, Supplementary Table S2 ) [ 61 ]. Additionally, the highly conserved 45S rDNA sequences were assembled in this study, and 5S rDNA sequences obtained from the 5S rDNA database ( , accessed on 3 October 2021) were also used to design probes with their highly conserved regions using FISH.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al. (2022) found that repetitive sequences in genomes of species of Prunus subgenus Cerasus are positively associated with the obvious genome size expansion that occurred in cherry and Japanese plum in the last 2 million years. This evidence supports the role of TEs as genome organizers (Figure 2) and contributors to genome evolution.…”
Section: Epigenetic Machinery In Plantsmentioning
confidence: 99%